Pengaruh Metode Pembelajaran Inkuiri dan Diskusi pada Materi Pokok Bentuk Aljabar terhadap Kemampuan Komunikasi dan Kemampuan Pemecahan Masalah Matematika - Ali Sadikin Wear; Renny Indrawati (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
The research is aimed to know; 1) interaction of inquiry learning  method application and discussion on communication ability and student’s mathematics  problem solving skills on multivariate. 2) the impacts of learning method on mathematics communication ability on univariat.3) the impacts of learning method on mathematics problem solving skills on univariat. This research is false experiment used non equivalent control group design with 2 factors  measurement technique. The instrument is essay test (problem solving and communication question). This research was conducted at public SMP in Palmerah distric, west Jakarta. The sample is the students of class VIII about 140 students. Data analyze used MANOVA analysis. The result of this research is: 1) there are significant impacts of learning method on communication ability and mathematics problem solving skills on multivariate. 2) there are significant impacts of learning method on mathematics communication ability on univariat 3) there isn’t significant impact of learning method on mathematics problem solving skill.